Research on the application progress of Tai Chi in the Prevention and treatment of major chronic diseases under the background of physical and health integration - Li, Huanhuan; Wu, Chunli; Jia, Gaoting (The Journal of the International Society of Chinese Health Practices, 2024)
See PDF for details